Medieval mystical women in the West growing in the height of love - Arblaster, John 1985-; Faesen, Rob 1958- (London New York Routledge Taylor & Francis Group, 2025)
"This book explores the rich and varied mystical writings by and about medieval and early modern women across Western Europe. Women had a profound and lasting impact on the development of medieval and early modern spiritual and mystical literature, both through their own writing and as a result of the hagiographical texts that they inspired. Bringing together contributions by both established and emerging scholars, the volume provides a valuable overview of medieval mystical women with a special focus on the Low Countries and Italy, regions that produced a disproportionately high number of female mystics. The figures discussed range from Hildegard of Bingen, Hadewijch, Mechthild of Magdeburg, Marguerite Porete, Angela of Foligno, Julian of Norwich and Beatrice of Nazareth to lesser-known women such as Agnes Blannbekin, Christina of Hane, and Maria Maddalena de' Pazzi. The chapters address topics such as the body, pain, desire, ecstasy, stigmata, annihilation, virtue, visions, the tension between exterior and interior experience, and the nature of mystical union itself"--
1. Mystical Hagiography in the Thirteenth Century: The Low Countries and Italy 2. Annihilated Women in the Thirteenth Century 3. Hidden Marks of Leadership: Holy Women and Invisible Stigmata in the Late Middle Ages 4. Enarrabiliter: The Separation of Visionary Experience and Communicable Form in Hildegard of Bingens Vision Books 5. Gender and Feminine Virtue in Bernard of Clairvaux and Hadewijch 6. Kenotic Christology, Poverty, and Annihilation in Clare of Assisi and Angela of Foligno 7. Mysticism by the Numbers: Beatrice of Nazareths Seven Manners of Love and Ida of Nivelles Eight Topics of Contemplation 8. Spiritual Edifices: Beatrice of Nazareths Monastery of the Heart and Agnes Blannbekins Urban Stations of Christ 9. The Mystic as Symbol: Ecstasy as Liturgical Participation in the Vita of Beatrice of Nazareth 10. I Want to Die Living: The Entanglement of Death and Desire in Mechthild of Magdeburg 11. Spiritual Vision in Corporeal Space: The Power of Performative Language in the Mystical Life of Christina of Hane 12. Can This Text Still Speak? Reading Julian of Norwichs Prayer for Illness as (Fully a Part of) a Classic Text of Embodied Mysticism 13. The Theological Virtues, Interiorisation, and Theological Anthropology in The Evangelical Pearl 14. The Blood and the Word: The Mystical Speech Acts of Maria Maddalena de Pazzi
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Women mystics -- Europe -- History; Mysticism -- Europe -- History -- Middle Ages, 600-1500; Christentum; Christianity; Gender Studies: Frauen und Mädchen; Gender studies: women; Geschichte der Religion; History of religion; LITERARY CRITICISM / Ancient & Classical; LITERARY CRITICISM / European / General; LITERARY CRITICISM / Women Authors; Literary studies: classical, early & medieval; Literaturwissenschaft: Antike und Mittelalter; RELIGION / Christianity / General; Religion / Christianity / History; RELIGION / Sexuality & Gender Studies; SOCIAL SCIENCE / Women's Studies; Western Continental Europe; Westeuropa; Aufsatzsammlung